Development of a real-time fluorescence loop-mediated isothermal amplification assay for rapid and quantitative detection of Ustilago maydis. Issue 1 (December 2017) - Cao, Yanyong; Wang, Lifeng; Duan, Liping; Li, Jingjing; Ma, Juan; Xie, Shuna; Shi, Lei; Li, Huiyong
Abstract The common smut of corn, caused byUstilago maydis is a troublesome disease of maize. Early and accurate detection ofU .maydis is essential for the disease management. In this study, primer set Pep-2 was selected for LAMP (loop-mediated isothermal amplification) from 12 sets of primers targeting threeU .maydis effector genesSee1, Pit2 andPep1 according to primer screening. The optimal concentrations ofBst DNA polymerase and Mg2+ as well as inner/outer primer ratio of the LAMP reaction system were screened by combining a single factor experiment and an orthogonal design arrangement. The specificity of this real-time LAMP (RealAmp) assay was confirmed by negative testing for other pathogens. The detection sensitivity of the RealAmp assay was 200 times higher than that of detection through conventional PCR. Results of the RealAmp assay for quantifying the genomic DNA ofU. maydis were confirmed by testing with both artificially and naturally infected samples. In addition, the RealAmp reaction could be conducted via an improved tube scanner to implement a "electricity free" assay from template preparation to quantitative detection. The resulting assay could be more convenient for use in the field as a simple, rapid, and effective technique for monitoringU. maydis .